Synthesis and Characterization of Rare Earth (Ce) Substituted Magnesium Ferrite MgCe0.1Fe1.9O4 and Banana Peel BPMgCe0.1Fe1.9O4 - ur Rehman, Atiq; Mukhtar Ahmad (Journal of Materials and Physical Sciences, 2020)
In this study, a composite of cerium doped magnesium ferrite (MgCexFe2-xO4 , x= 0.1) and banana peel powder was prepared by hydrothermal method. Crystal structure and phase identification, chemical bonding, and magnetic properties were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) and vibrating sample magnetometery (VSM), respectively. XRD results reveal that the prepared ferrite exhibits single phase face centered cubic (fcc) structure having no impurity in the sample. Addition of banana peel powder has no effect on the crystal structure. The values of structural parameters greatly match with the earlier reported values for the same structure. FTIR results clearly indicate that the prepared ferrite is spinel and have well defined vibrational and stretching peaks due to different molecules present in the compound. Coercivity values for both ferrite and composite materials are found to be a few hundred Oersted which confirm the soft magnetic nature of this ferrite. The observed parameters show that the prepared composite may find technological application for microwave absorption and multi-layer chip inductors.